Peningkatan Proses Pembelajaran IPS Menggunakan Metode Simulation terhadap Pemahaman Konsep Ekonomi Sekolah Dasar - Vani Qhairum Nisa Utami; Yeni Erita; Didi Syahrir; Ranianisa Rahmi (MODELING: Jurnal Program Studi PGMI, 2023)
This study aims to find out whether the simulation approach in teaching social studies in grade V at an elementary school can improve social studies learning. Classroom action research (PTK), which combines qualitative and quantitative methods, was the type of research used. In total, there were 22 students in class V. Cycle I experienced an increase in lesson plan observation results of 81.91%, and cycle II experienced an increase of 97.22%. The observation results of teacher characteristics in cycle I amounted to 82.81%, and increased to 93.75% in cycle II. The results of observations of student characteristics in cycles I and II were 82.81% and 93.75%, respectively. This shows that the social studies learning process in class V SDN 32 Andalas has improved by using the simulation method.